Acupuncture as anticancer treatment? - Frączek, Paulina; Kilian-Kita, Aneta; Püsküllüoglu, Mirosława; Krzemieniecki, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2016)
The mystery of Traditional Chinese Medicine has been attracting people for years. Acupuncture, ranked among the most common services of Complementary and Alternative Medicine, has recently gained a lot of interest in the scientific world. Contemporary researchers have been continuously trying to shed light on its possible mechanism of action in human organism. Numerous studies pertaining to acupuncture’s application in cancer symptoms or treatment-related side effects management have already been published. Moreover, since the modern idea of acupuncture’s immunomodulating effect seems to be promising, scientists have propounded a concept of its potential application as part of direct anti-tumor therapy. In our previous study we summarized possible use of acupuncture in management of cancer symptoms and treatment-related ailments, such as chemotherapy-induced nausea and vomiting, pain, xerostomia, vasomotor symptoms, neutropenia, fatigue, anxiety, insomnia, lymphoedema after mastectomy and peripheral neuropathy. This article reviews the studies concerning acupuncture as a possible tool in modern anticancer treatment.